IMPLEMENTATION OF THE MUSAQAH AGREEMENT IN OIL PALM LAND MANAGEMENT IN KARANG JAYA VILLAGE, MUKOMUKO REGENCY - Tasdiq, M.Baqilani; Eka Sri Wahyuni; Miko Polindi (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
This study aims to analyze the implementation of musaqah contracts in oil palm plantation management in Karang Jaya Village, Mukomuko Regency. The research used a descriptive qualitative method with data collected through observation, interviews, and documentation. The subjects were landowner and cultivators involved in musaqah cooperation. The results show that musaqah practices in Karang Jaya Village are primarily conducted through oral agreements without written agreements and without a clear time frame. Profit-sharing is generally distributed equally between the two parties. However, several issues arise, such as lack of transparency, and unclear agreements. From an Islamic legal perspective, musaqah contracts are permissible, but improvements are needed in the clarity of contracts, profit distribution, and documentation to align with the principles of Islamic justice